2018
DOI: 10.1007/s00394-018-1814-y
|View full text |Cite
|
Sign up to set email alerts
|

The amounts and contributions of total drinking fluids and water from food to total water intake of young adults in Baoding, China

Abstract: A large proportion of young adults have insufficient TWI. Participants with lower TWI would not compensate with water from food. The variances in TWI among participants were mainly due to differences in total drinking fluids. There is an urgent need to improve the fluids intake behaviors of young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 49 publications
2
39
1
Order By: Relevance
“…Men generally have a higher metabolic rate than women at the same age due to the physiological disparity, and hence, the fluid requirements for men are higher than those for women. Several studies in China have reported that males had a higher fluid consumption than females among primary, middle school students [16][17][18], college students [23,33], and adults [13,14]. Our result is in accordance with these findings of China.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Men generally have a higher metabolic rate than women at the same age due to the physiological disparity, and hence, the fluid requirements for men are higher than those for women. Several studies in China have reported that males had a higher fluid consumption than females among primary, middle school students [16][17][18], college students [23,33], and adults [13,14]. Our result is in accordance with these findings of China.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the median daily fluid intake was 1050 mL, which was lower than the findings of a survey of adults aged 18-55 years in 27 Chinese cities (1214 mL) [14] and a survey among young adults aged 18-23 years in Baoding, China (1135 mL) [33]. These differences may be due to the different climate conditions and characteristics of the study populations.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…T According to the General standard for beverages of China (GB/T 1-789-2015) [42], all the drinking fluids were classified as below: water (plain water, tap water and bottle water), tea (fermented tea and semifermented tea), milk and milk products (liquid milk, yogurt and other milk products), SSBs (carbonated drinks, sports drinks, sweetened fruit juice, vegetable juice, protein drinks and other sugared drinks), alcohols(wine, beer, liquor, etc.) and other beverages [43].…”
Section: Measurement Of Total Water Intakementioning
confidence: 99%
“…), dishes (vegetables, meat, fish and eggs), porridge (millet porridge and other porridges), soup (tomato egg soup and other soups) and snacks (fruits, nuts, etc.) [43].…”
Section: Measurement Of Total Water Intakementioning
confidence: 99%